Crustal Azimuthal Anisotropy Beneath the Central North China Craton Revealed by Receiver Functions. (9th May 2019) - Zheng, Tuo; Ding, Zhifeng; Ning, Jieyuan; Liu, Kelly H.; Gao, Stephen S.; Chang, Lijun; Kong, Fansheng; Fan, Xiaoping
Abstract: To characterize crustal anisotropy beneath the central North China Craton (CNCC), we apply a recently developed deconvolution approach to effectively remove near‐surface reverberations in the receiver functions recorded at 200 broadband seismic stations and subsequently determine the fast orientation and the magnitude of crustal azimuthal anisotropy by fitting the sinusoidal moveout of the P to S converted phases from the Moho and intracrustal discontinuities. The magnitude of crustal anisotropy is found to range from 0.06 s to 0.54 s, with an average of 0.25 ± 0.08 s. Fault‐parallel anisotropy in the seismically active Zhangjiakou‐Penglai Fault Zone is significant and could be related to fluid‐filled fractures. Historical strong earthquakes mainly occurred in the fault zone segments with significant crustal anisotropy, suggesting that the measured crustal anisotropy is closely related to the degree of crustal deformation. The observed spatial distribution of crustal anisotropy suggests that the northwestern terminus of the fault zone probably ends at about 114°E. Also observed is a sharp contrast in the fast orientations between the western and eastern Yanshan Uplifts separated by the North‐South Gravity Lineament. The NW‐SE trending anisotropy in the western Yanshan Uplift is attributable to "fossil" crustal anisotropy due to lithospheric extension of the CNCC, while extensional fluid‐saturated microcracks induced by regional compressive stress are responsible for the observed ENE‐WSW trending anisotropy in the eastern Yanshan Uplift. Comparison of crustal anisotropy measurements and previously determined upper mantle anisotropy implies that the degree of crust‐mantle coupling in the CNCC varies spatially. Key Points: Crustal anisotropy in the central North China Craton is measured at 112 seismic stations using moveout of P ‐to‐ S converted phases Significant crustal anisotropy in the Zhangjiakou‐Penglai Fault Zone is closely related to the degree of crustal deformation Contrasting difference in the fast orientations is revealed between the western and eastern Yanshan Uplifts